Study of density and distribution of mast cells in endometrium - Renuka M. Patil; Nida Nausheen; Saeed Yendigeri (Al Ameen Medical College, 2023)
Introduction: Mast cells are heterogenous group of immune cells involved in multiple biological events they play vital role in various inflammatory and immunological reactions, linking humoral and cell mediated phases of processes. Aim and Objective: In this study we have tried to compare the density and distribution of mast cells in various endometrial lesions. Material and Methods: A prospective study with 101 cases of post hysterectomy were studied. Hysterectomy specimens were cut open from anterior wall, incorporated endometrium and myometrium, fixed in 10% formalin after routine processing, embedded in paraffin, 5 micron thickness section taken and stained with Haematoxillin-Eosin, and toludine blue to visualize mast cells. Results: It showed a significant p value which was < 0.001. Conclusion: Mast cell profile may be an additional diagnostic/prognostic tool in different endometrial lesions.